Usefulness of parasitologic and serologic studies in the diagnosis of human strongyloidiasis. Metaanallysis execise - Huapaya, Pedro (2002)
Objective: To conduct metaanalysis by reviewing bibliographic references published during the last 20 years that directly or indirectly compared serologic and parasitologic diagnostic methods for Strongyloides stercoralis infection. Material and methods: We tried to build a tetracoric table to obtain values of serology sensitivity and specificity, choosing parasitologic methods as gold standard. Finally, those references that compared ELISA with parasitologic methods were selected and information was obtained to calculate positive and negative predictive values. Results: Twenty-five references were chosen by applying selection criteria. Positive and negative predictive values were 85,33% and 97,83%, respectively. Conclusion: These results show the potential usefulness of ELISA method as a screening test for strongyloidiasis, in order to facilitate studies in populations exposed to this potentially lethal parasite.